Contact pressure explains half of the abdominal aortic aneurysms wall thickness inter-study variability - Kracík, Jan; Kubíček, Luboš; Staffa, Robert; Polzer, Stanislav (PloS one, 2024)
The stochastic rupture risk assessment of an abdominal aortic aneurysm (AAA) critically depends on sufficient data set size that would allow for the proper distribution estimate. However, in most published cases, the data sets comprise no more than 100 samples, which is deemed insufficient to describe the tails of AAA wall thickness distribution correctly. In this study, we propose a stochastic Bayesian model to merge thickness data from various groups. The thickness data adapted from the literature were supplemented by additional data from 81 patients. The wall thickness was measured at two different contact pressures for 34 cases, which allowed us to estimate the radial stiffness. Herein, the proposed stochastic model is formulated to predict the undeformed wall thickness. Furthermore, the model is able to handle data published solely as summary statistics. After accounting for the different contact pressures, the differences in the medians reported by individual groups decreased by 45%. Combined data can be fitted with a lognormal distribution with parameters μ = 0.85 and σ = 0.32 which can be further used in stochastic analyses.
Keywords: Male; stochastické procesy; aneurysma břišní aorty; Bayes Theorem; ruptura aorty; Aortic Rupture; Aged; mužské pohlaví; senioři; aorta abdominalis; lidé; ženské pohlaví; Stochastic Processes; Humans; Aorta, Abdominal; Pressure; tlak; Bayesova věta; Aortic Aneurysm, Abdominal; Female